2002
DOI: 10.1089/104303402760128577
|View full text |Cite
|
Sign up to set email alerts
|

A Phase II, Double-Blind, Randomized, Placebo-Controlled Clinical Trial of tgAAVCF Using Maxillary Sinus Delivery in Patients with Cystic Fibrosis with Antrostomies

Abstract: tgAAVCF, an adeno-associated cystic fibrosis transmembrane conductance regulator (CFTR) viral vector/gene construct, was administered to 23 patients in a Phase II, double-blind, randomized, placebo-controlled clinical trial. For each patient, a dose of 100,000 replication units of tgAAVCF was administered to one maxillary sinus, while the contralateral maxillary sinus received a placebo treatment, thereby establishing an inpatient control. Neither the primary efficacy endpoint, defined as the rate of relapse o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
131
0
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 237 publications
(134 citation statements)
references
References 28 publications
1
131
0
2
Order By: Relevance
“…The favorable properties of AAV vectors have permitted its entry into human clinical studies for diseases such as cystic fibrosis [26,27], Canavan disease [28] and hemophilia B [29]. The luminal gastrointestinal tract, as a target for gene transfer, could provide a therapeutic strategy and aid research to help decipher the pathogenesis of a variety of epitheliumderived diseases such as IBDs, hemochromatosis and intestinal cancers.…”
Section: Discussionmentioning
confidence: 99%
“…The favorable properties of AAV vectors have permitted its entry into human clinical studies for diseases such as cystic fibrosis [26,27], Canavan disease [28] and hemophilia B [29]. The luminal gastrointestinal tract, as a target for gene transfer, could provide a therapeutic strategy and aid research to help decipher the pathogenesis of a variety of epitheliumderived diseases such as IBDs, hemochromatosis and intestinal cancers.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14][15][16][17] Several early-phase clinical trials with AAV vectors have been initiated and shown to be safe. [18][19][20][21] Among the at least eight different AAV natural serotypes discovered so far, AAV vector derived from serotype 2 (AAV2) has been the most extensive studied and widely used AAV vector in the past 20 years. However, neutralizing antibodies against AAV2 exist in a large human population, 22,23 and relative transduction efficiency of AAV2 in liver is less than 10% in hepatocytes.…”
Section: Introductionmentioning
confidence: 99%
“…It is, nonetheless, tempting to speculate that at the very least, the therapeutic vector dosage could be reduced by a log to overcome problems associated with vector load and immune response seen in clinical trials. 35 Furthermore, given that AAV2 remains the sole serotype vector currently in use in human gene therapy, 20,21,[36][37][38][39][40] coupled with the fact that it is also the best characterized in terms of vector toxicology, it is conceivable that this strategy could be employed to augment transgene expression scAAV2-TC-PTP and scAAV2-PP5 as helper viruses for ssAAV2 vectors GR Jayandharan et al from single-stranded vectors containing large genes such as coagulation factor VIII in the liver in clinical trials in patients with hemophilia A. In our current studies, the TC-PTP and the PP5 genes were under the control of the RSV promoter.…”
mentioning
confidence: 99%